Existence of positive solutions of some integral equations - Ligęza, Jan (Annales Mathematicae Silesianae, 2004)
We study the existence of positive solutions of the integral equation x(t) = ∫01k(t,s)f(s,x(s),x's),...,x(n-1)(s))ds, n≥2 in both Cn-1[0,1] and Wn-1,p[0,1] spaces, where p≥1. The Krasnosielskii fixed point theorem on cone is used.